Travel and ethnology in the Renaissance : South India through European eyes, 1250-1625 - Rubiés, Joan Pau (Past and present publications., 2000)
This book is a major contribution to the study of the encounter between Europeans and non-Europeans in the early modern period and to a neglected aspect of the cultural transformation of Europe throughout the Renaissance. The book proposes a novel approach to the study of European attitudes towards non-Europeans.